2012
DOI: 10.2500/ajra.2012.26.3788
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Volume Turbinate Reduction versus Partial Turbinectomy: Clinical and Histological Features

Abstract: In our study both surgical techniques achieved good clinical outcomes with improved nasal function, although the ciliated epithelium appeared partially impaired. These findings resulted in a prolonged MCT in all patients, especially in those treated with partial turbinectomy. Compared to partial resection, intraturbinal turbinate reduction seems to be the method of choice to better preserve nasal physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…There have been studies that have reported preoperative findings of epithelial metaplasia and loss of ciliated cells . On the other hand, there are studies that have shown a normal appearance of the epithelium with a preserved number of cilia . In the present study, squamous metaplasia and total loss of ciliated cells were found in the majority of the preoperative samples.…”
Section: Discussionsupporting
confidence: 45%
“…There have been studies that have reported preoperative findings of epithelial metaplasia and loss of ciliated cells . On the other hand, there are studies that have shown a normal appearance of the epithelium with a preserved number of cilia . In the present study, squamous metaplasia and total loss of ciliated cells were found in the majority of the preoperative samples.…”
Section: Discussionsupporting
confidence: 45%
“…Techniques for turbinate reduction should reliably reduce nasal obstruction while maintaining normal mucosal function and limiting the propensity for complications such as bleeding and crusting. 8,9 In our study, reduction of inferior turbinate and relief of nasal obstruction was best achieved with the endoscopic medial flap turbinoplasty technique. There was a sustained benefit at 60 months after the surgical procedure with good examiner and patient scores.…”
Section: Discussionmentioning
confidence: 87%
“…Rhee et al [16] compared RFA with laser-vaporizing turbinoplasty. Similarly, Garzaro et al [17] found both RFA and partial turbinectomy affect nasal mucociliary clearance, but mucociliary transport time was more prolonged in patients treated with partial turbinectomy. Similarly, Garzaro et al [17] found both RFA and partial turbinectomy affect nasal mucociliary clearance, but mucociliary transport time was more prolonged in patients treated with partial turbinectomy.…”
Section: Outcomementioning
confidence: 81%
“…With respect to nasal mucociliary function, several studies have been published [16][17][18]. Rhee et al [16] compared RFA with laser-vaporizing turbinoplasty.…”
Section: Outcomementioning
confidence: 99%